2018
DOI: 10.1159/000493255
|View full text |Cite
|
Sign up to set email alerts
|

Poorly Differentiated Small-Cell-Type Neuroendocrine Carcinoma of the Prostate: A Case Report and Literature Review

Abstract: Neuroendocrine cells are widespread throughout the body and can give rise of neuroendocrine tumors due to abnormal growth of the chromaffin cells. Neuroendocrine tumors divide into many subtypes based on tumor grade (Ki-67 index and mitotic count) and differentiation. These tumors can be further divided into secretory and nonsecretory types based on the production of peptide hormone by tumor cells. Poorly differentiated small-cell-type neuroendocrine tumors are one of the subtypes of neuroendocrine tumors. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Our study is the most representative and comprehensive of the latest primary survival information of NEC compared with the most common histological type of prostate cancer. Given that NEPC is a rare and highly aggressive malignancy, majority of investigations are based on case reports or retrospective studies limited by small sample sizes (13)(14)(15)(16)(17). Consequently, the present study performed an investigation of a prostate cancer patient cohort based on large population from SEER registries between 2004 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Our study is the most representative and comprehensive of the latest primary survival information of NEC compared with the most common histological type of prostate cancer. Given that NEPC is a rare and highly aggressive malignancy, majority of investigations are based on case reports or retrospective studies limited by small sample sizes (13)(14)(15)(16)(17). Consequently, the present study performed an investigation of a prostate cancer patient cohort based on large population from SEER registries between 2004 and 2018.…”
Section: Discussionmentioning
confidence: 99%
“…The rarity of primary NEPC means that most available studies to date have been case reports. [7][8][9][10][11] Zaffuto et al 12 Although the difference between the median survival times was statistically significant, this did not translate into a notable clinical difference. Most T-SCNCs present initially as prostate adenocarcinomas, which then undergo neuroendocrine (NE) differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…The rarity of primary NEPC means that most available studies to date have been case reports . Zaffuto et al and Alanee et al explored the differences in prognostic and clinical data between patients with the small‐cell carcinoma (SCC) subtype of NEPC and those with non‐SCC NEPC.…”
Section: Introductionmentioning
confidence: 99%
“…Our study adds to the existing case reports and cohort studies that have reported on outcomes from other parts of the world 1,13,14 . For example, Horne et al presented on 800 patients with SCPC from the National Cancer Database, US, diagnosed between 2004 and 2015 15 .…”
Section: Discussionmentioning
confidence: 85%